نظام تمويل السكن في الجزائر مع عرض تجارب دولية - منصور عبد النور (جامعة البليدة2-كلية العلوم الإقتصادية والعلوم التجاريةوعلوم التسيير, 2019)
لملخص:** نتناول في هذه الدراسة موضوع تمويل السكن في الجزائر، من خلال دراسة نظام تمويل السكن ومحاولة معرفة طريقة سيره؛ بالوقوف على جميع الأطراف المشاركة فيه من البنوك التجارية والمؤسسات المالية المانحة للقروض العقارية، ودور الدولة في إنجاحه، وذلك للإجابة على إشكالية الدراسة المتمثلة في مدى مساهمة نظام تمويل السكن في حل أزمة السكن في الجزائر. تهدف دراستنا إلى محاولة تشخيص وتقييم نظام تمويل السكن في الجزائر وتبيان النقائص فيه، مع اقتراح الحلول الممكنة لتطويره بالاعتماد على تجارب دولية ناجحة واستخلاص الدروس منها ودراسة إمكانية تطبيقها على الجزائر؛ حيث قمنا في دراستنا بالتطرق أولاً إلى مفاهيم عامة حول تمويل السكن ببيان أهمية السكن للإنسان وكذا الحاجة إلى توفير التمويل لقطاع السكن، ثم تطرقنا إلى قطاع السكن في الجزائر بعرض تطوراته من الاستقلال إلى يومنا هذا وتبيان وضعية الحظيرة السكنية في الجزائر؛ التي تعاني من عجز كبير في العرض ويقابله الطلب المرتفع والمستمر على السكن، ثم قدمنا عرضاً للتجارب الدولية الناجحة في تمويل السكن ممثلة في دول سنغافورة، ماليزيا وكندا، وفي الأخير قمنا بتقييم نظام تمويل السكن في الجزائر مع تقديم اقتراحات وحلول استناداً إلى تجارب الدول السابق ذكرها. توصلنا في دراستنا إلى عدة نتائج أهمها أن الدولة الجزائرية بذلت جهوداً كبيرة لحل مشكل السكن وخصصت مبالغ مالية معتبرة للقضاء عليه خاصة في المخططين الخماسيين الأخيرين (2010 - 2014) و(2015 - 2019)؛ حيث قلصت من الفجوة بين العرض والطلب كما تم طرح صيغ سكنية متعددة للاستجابة لمتطلبات المواطنين. كما قامت الدولة بعدة إصلاحات على نظام تمويل السكن بإنشاء عدة مؤسسات مالية متخصصة في تمويل السكن لإشراك البنوك في تمويل السكن، إلا أنه رغم الإجراءات المتخذة فإن البنوك التجارية ما زالت تعزف عن منح القروض العقارية وتفضل التوجه نحو قطاعات أكثر ربحية، وهو ما يتطلب ضرورة تفعيل نظام تمويل السكن بجعله أكثر مرونة، وتخفيف الإجراءات الإدارية في عملية منح القروض ودراسة الملفات، مع ضرورة الاستفادة من تجارب الدول التي ذكرناها في هذا المجال، والتي أعطت الأولوية لقطاع السكن بوضع مؤسسات مالية متخصصة في تمويل السكن، والتي عملت بفعالية وكفاءة عالية؛ وهو ما انعكس إيجاباً على قطاع السكن وتمكنت من توفير السكن لمواطنيها بنسبة كبيرة. **الكلمات المفتاحية:** تمويل السكن، نظام التمويل، القروض العقارية، قطاع السكن.Abstract : In this study, we discuss the subject of housing finance in Algeria, through studying the housing finance system and trying to find how it work, by standing on all participating in it from commercial banks, and financial institutions that lend real estate loans and the role of the state in making it success. In order to answer the question of the study which is the contribution of the housing finance system to solve the housing crisis in Algeria. Our study aims at trying to diagnose and evaluate the housing finance system in Algeria and Showing the shortcomings in it, and propose possible solutions for its development based on successful international experiences, lessons learned and study of their applicability to Algeria. In our study we first discussed general concepts of housing finance, As well as the need to provide financing for the housing sector. Then we discussed the housing sector in Algeria by presenting its developments from independence to the present day, and indicating the status of the housing in Algeria; which suffers from a large supply deficit which is offset by a high and continuous demand for housing. In addition we present the successful international experiences in housing finance represented in the countries of Singapore Malaysia and Canada, finally we evaluated the housing finance system in Algeria with the submission of proposals and solutions based on the experiences of the countries mentioned above. In our study, we reached several results, the most important is that the Algerian state has made great efforts to solve the problem of housing and allocated large sums of money to eliminate it, especially in the last tow planners (2010-2014) and (2015-2019), which reduced the gap between supply and demand. In addition, several housing forms have been put in to respond to citizens' demands. The State has also made reforms to the housing finance system by establishing financial institutions specialized in housing finance to involve banks in housing finance. However, despite the measures taken, commercial banks are still reluctant to grant mortgages and prefer more profitable sectors, which requires to activate the housing finance system by making it more flexible, and easing administrative procedures in the process of granting loans and study files, With the need to benefit from the experiences of the countries mentioned, which gave priority to the housing sector by the establishment of financial institutions specialized in housing finance, which worked effectively and efficiently; that reflected positively on the housing sector and was able to provide housing for its citizens with a large percentage. Keywords: housing finance, finance system, mortgages, housing sector.
Keywords: تمويل السكن; نظام التمويل; القروض العقارية; قطاع السكن; السكن في الجزائر; تمويل السكن في الجزائر; تجارب دولية